2020
DOI: 10.3390/cancers12113343
|View full text |Cite
|
Sign up to set email alerts
|

The Polemic Diagnostic Role of TP53 Mutations in Liquid Biopsies from Breast, Colon and Lung Cancers

Abstract: Being minimally invasive and thus allowing repeated measures over time, liquid biopsies are taking over traditional solid biopsies in certain circumstances such as those for unreachable tumors, very early stages or treatment monitoring. However, regarding TP53 mutation status analysis, liquid biopsies have not yet substituted tissue samples, mainly due to the lack of concordance between the two types of biopsies. This needs to be examined in a study-dependent manner, taking into account the particular type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Approximately, 19.1% of patients carried TP53 mutations are in accordance with the previous studies, which reported the frequency of somatic TP53 mutations ranging from 15% to 71%. Somatic TP53 mutation leads to disruption in the cell cycle, induced apoptosis, and affected DNA damage repair process, and the presence of TP53 mutations in cfDNA was associated with lower PFS independently of clinical treatment [ 18 ]. Approximately 17.6% of patients carried PIK3CA mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, 19.1% of patients carried TP53 mutations are in accordance with the previous studies, which reported the frequency of somatic TP53 mutations ranging from 15% to 71%. Somatic TP53 mutation leads to disruption in the cell cycle, induced apoptosis, and affected DNA damage repair process, and the presence of TP53 mutations in cfDNA was associated with lower PFS independently of clinical treatment [ 18 ]. Approximately 17.6% of patients carried PIK3CA mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Gene mutations in cfDNA have shown some prognostic significance, and these mutations can be detected in plasma cfDNA by next generation sequencing (NGS) [ 1 ]. There is a clear correlation between presence of TP53 mutations in cfDNA and adverse progression-free survival (PFS) outcome [ 18 ]. Several retrospective studies have also reported that ESR1 or PIK3CA mutations were related to shorter PFS and overall survival (OS) in hormone receptor- (HR-) positive metastatic BC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of TP53 mutation frequency in cfDNA varies from 31% to about 50% across studies [ 141 , 142 ]. On the other hand, the reported VAF of TP53 mutations in plasma have a broader variation than mutation rate, ranging from 0.09% to 70% across different reports [ 143 ]. A meta-analysis which reported a mutation rate of 37.8% for TP53 in cfDNA independent of tumor stage indicated that TP53 mutations were associated with recurrence, short disease-free survival (DFS), and PFS.…”
Section: Use Of Digital Pcr In Ctdna Analysis In Breast Cancer Patientsmentioning
confidence: 99%
“…This mechanism of neoplastic transformation mediated by ctDNA has been proved in fibroblastic cell cultures [ 86 ] or CRC and pancreatic-cell-line models [ 87 , 88 ]. It was also assumed that distant metastases in CRC may be formed as a result of the transfection of normal cells located in the target organs, with ctDNA harboring mutations in the TP53 , KRAS , and HBB genes [ 89 , 90 ]. Furthermore, CRC-derived ctDNA increased, in vitro, the expression of the mRNA level of 118 genes, which included genes with metastatic potentials, such as INSIG1 , CREB3L2 , CEACAM5 , LIPG , or DAPP1 [ 91 ].…”
Section: Role Of Ctcs and Ctdna In Metastatic Spreadmentioning
confidence: 99%